Modeling, methodologies and tools for molecular and nano-scale communications : modeling, methodologies and tools - Suzuki, Junichi; Nakano, Tadashi; Moore, Michael John (Modeling and Optimization in Science and Technologies, 2017)
This volume reports on cutting-edge modeling techniques, methodologies and tools used to understand, design and engineer nanoscale communication systems, such as molecular communication systems. Moreover, it includes introductory materials for those who are new to the field. The book's interdisciplinary approach, which merges perspectives in computer science, the biological sciences and nanotechnology, will appeal to graduate students and researchers in these three areas.